1987
DOI: 10.1007/bf00279615
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 dose-dependently affects the biosynthesis of (pro)insulin in isolated rat islets of Langerhans

Abstract: Human crude and recombinant interleukin 1 (IL-1) was found to dose- and time-dependently affect the biosynthesis of (pro)insulin in isolated rat islets of Langerhans. Incubation of rat islets with either 0.5 U/ml or 5 U/ml of crude IL-1 for 1 h had no detectable effect on (pro)insulin biosynthesis. After 24 hours of exposure 0.5 U/ml of crude or 0.6 ng/ml of recombinant IL-1 (beta) increased the (pro)insulin biosynthesis by 42% and 58%, respectively, whereas a 10-fold greater concentration of IL-1 decreased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 33 publications
4
43
0
Order By: Relevance
“…Similar findings were observed in INS-1E cells exposed to thapsigargin or cytokines (IFN-γ plus IL-1β) and in primary beta cells exposed to the same agents. Cytokines inhibit Ins1/2 mRNA expression and pro-insulin biosynthesis in rat and mouse islets [46][47][48]. The decrease in Ins1/2 levels is secondary to NO production [22], a finding confirmed in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were observed in INS-1E cells exposed to thapsigargin or cytokines (IFN-γ plus IL-1β) and in primary beta cells exposed to the same agents. Cytokines inhibit Ins1/2 mRNA expression and pro-insulin biosynthesis in rat and mouse islets [46][47][48]. The decrease in Ins1/2 levels is secondary to NO production [22], a finding confirmed in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Protein synthesis, chaperones, and protein folding. Several studies have shown IL-1 to influence gene transcription and protein synthesis (12,14,25,43) and have shown IL-1 to cause a fall in the overall rate of protein synthesis and of preproinsulin biosynthesis in particular (44).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β has been shown to inhibit gene transcription and protein synthesis [13,33] and to decrease preproinsulin biosynthesis in particular [34]. Therefore, a global decrease in protein synthesis could reduce the capacity of a beta cell to survive IL-1β exposure.…”
Section: Protein Synthesis Chaperones and Protein Foldingmentioning
confidence: 99%